2013
DOI: 10.1016/j.fas.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-associated stem cell transplantation (MAST) in chondral defects of foot and ankle is effective

Abstract: MAST led to good clinical scores. No complications were registered. Even though a control group is missing, we conclude that MAST is a safe and effective method for the treatment of chondral defects. The main advantage of MAST in comparison with ACI and MACI is the single procedure methodology. The advantage in comparison with AMIC is the potential higher concentration of stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Finally, Richter et al [ 35 ] investigated the outcomes offered by BMSCs onto a collagen matrix for chondral ankle lesions, confirming no complications and a promising clinical improvement at 24 months of follow-up.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, Richter et al [ 35 ] investigated the outcomes offered by BMSCs onto a collagen matrix for chondral ankle lesions, confirming no complications and a promising clinical improvement at 24 months of follow-up.…”
Section: Resultsmentioning
confidence: 97%
“… The quality of cartilage further improved at MRI at 24 months Wong [ 24 ] 2013 Arthroscopy RCT IA injection Comb HTO + MFX and post-op injection Knee OA 28 BMSCs + HA 28 HA 24 months BMSCs i.a. injection produced superior clinical and MRI outcomes at 24 months Ricther [ 35 ] 2013 Foot & Ankle Case series Surgical delivery MAST Collagen membrane Ankle chondral defects 25 24 months No adverse events. Clinical scores improvement Positive findings at histology Orozco [ 22 ] 2013 Transplantation Case series IA injection Knee OA 12 12 months No safety issues.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding open foot and ankle chondral defect repairs, implantation of nonexpanded BMC-impregnated collagen matrix was reported by Richter and Zech 94 in 25 patients who were followed up with at 2 years with significant improvements in VAS foot and ankle scores.…”
Section: Methods Of Stem Cell Transplantationmentioning
confidence: 96%
“…Richter et al 41 published the clinical assessment of a matrix-associated stem cell implantation strategy with a 2-year follow-up in chondral defects of the foot and ankle (figure 6). That interesting study evaluated 25 patients and showed good clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…(A) A large defect (6 cm 2 ) at the entire talar dome after debridement; (B) the defect after microfracturing and (C) the matrix with cells in vivo. (Adapted from: Richter et al 41. ).…”
Section: Introductionmentioning
confidence: 99%